A Case of Congenital Leukemia With MYB-GATA1 Fusion Gene in a Female Patient. Issue 1 (January 2022) - Ozono, Shuichi; Yano, Shoichiro; Oishi, Saori; Mitsuo, Miho; Nakagawa, Shinichiro; Toki, Tsutomu; Terui, Kiminori; Ito, Etsuro
Abstract : We report a female newborn with acute myelogenous leukemia (AML) associated with a MYB-GATA1 fusion gene. Morphologic findings of myeloid lineage were obtained using light microscopy. Cytogenetic analysis of peripheral blood showed a complex karyotype: 46, X, -X, add(3)(q21), der(6)add(6)(q21)del(6)(q?), +mar1[5]/46, XX[15]. Targeted RNA sequencing revealed a MYB-GATA1 fusion gene. Reduced-dose AML-type chemotherapy resulted in remission and survival for >3 years without relapse. The present case demonstrated the feasibility of carrying out targeted RNA sequencing for identifying MYB-GATA1 and supports the notion that neonatal AML with MYB-GATA1 with reduced chemotherapy may show better prognosis than other highly toxic therapies. Abstract : Supplemental Digital Content is available in the text.